Tinjauan Hukum tentang Kebijakan Persaingan Usaha dan Implikasinya pada Bisnis Startup - Maulana, Arman (Koaliansi : Cooperative Journal, 2023)
This study aims to conduct a legal review of business competition policy and its implications for startup businesses in Indonesia. Through the literature review method, various relevant literature sources such as laws, regulations, court decisions, scientific journals, and books related to business law and startups are identified, collected, and qualitatively analyzed. The results of the study show that business competition policy has a significant impact on startup businesses. The implications faced by startup businesses include licensing requirements, restrictions on certain business practices, strict supervision, and potential legal sanctions. A clear and consistent business competition policy is an important factor in creating a fair, transparent and competitive business environment for startup business people. However, challenges also occur, such as legal uncertainty, limited access to information, and limited legal resources owned by startup businesses. Therefore, supporting steps are needed, including increasing legal clarification, legal assistance and guidance, as well as collaboration with communities and startup business associations.